REKONSTRUKSI UNDANG-UNDANG PERKAWINAN (UNDANG-UNDANG NO.1 TAHUN 1974) TENTANG BATAS USIA PERKAWINAN - Yulies Tiena Masriani Yulies Tiena Masriani (FEB UNTAG Semarang, 2013)
Reconstruction of Marriage Act (Act No. 1 of 1974) About Marriage Age Limit viewed from the aspect of philosophical, juridical and sociological, returned to the provisions of 19 year old men and women 16 years (Article 7, paragraph 1), so that the rights of children are protected. While marriage without parental consent, according to the Marriage Act may be canceled, if the parties do not meet the requirements to establish a marriage. Similarly, according to Islamic law, a marriage without parental consent as guardian illegitimate, or executed by the trustee is not entitled, may be canceled. Annulment of a marriage begins after court ruling has binding legal force and effect from the time of the marriage. And this decision does not apply retroactively to children born of the marriage.